Association of metformin use with fracture risk in type 2 diabetes: A systematic review and meta-analysis of observational studies - Wang, Yining; Yu, Liming; Ye, Zhiqiang; Lin, Rui; Sun, Antonia RuJia; Liu, Lingna; Wei, Jinsong; Deng, Feifu; Zhong, Xiangxin; Cui, Liao; Li, Li; Liu, Yanzhi (Frontiers in Endocrinology, 2023)
Aims Increasing evidence suggests that metformin can affect bone metabolism beyond its hypoglycemic effects in diabetic patients. However, the effects of metformin on fracture risk in type 2 diabetes mellitus (T2DM) patients remain unclear. A systematic review and meta-analysis were performed in this study to evaluate the association between metformin application and fracture risk in T2DM patients based on previous studies published until June 2021. Methods A systematic search was performed to collect publications on metformin application in T2DM patients based on PubMed, Embase, Cochran, and Web of Science databases. Meta-analysis was performed by using a random-effects model to estimate the summary relative risks (RRs) with 95% confidence intervals (CIs). Subgroup analyses based on cohort/case-control and ethnicity and sensitivity analyses were also performed. Results Eleven studies were included in the meta-analysis. Results demonstrated metformin use was not significantly associated with a decreased risk of fracture (RR, 0.91; 95% CI, 0.81–1.02; I2 = 96.8%). Moreover, metformin use also demonstrated similar results in subgroup analyses of seven cohort studies and four case-control studies, respectively (RR, 0.90; 95% CI, 0.76–1.07; I2 = 98.0%; RR, 0.96; 96% CI, 0.89–1.03; I2 = 53.7%). Sensitivity analysis revealed that there was no publication bias. Conclusion There was no significant correlation between fracture risk and metformin application in T2DM patients. Due to a limited number of existing studies, further research is needed to make a definite conclusion for clinical consensus.